Atypical Non-H2S-Producing Monophasic Salmonella Typhimurium ST3478 Strains from Chicken Meat at Processing Stage Are Adapted to Diverse Stresses - Mourao, J (2020)
Poultry products are still an important cause of Salmonella infections worldwide, with an increasingly reported expansion of less-frequent serotypes or atypical strains that are frequently multidrug-resistant. Nevertheless, the ability of Salmonella to survive antimicrobials promoted in the context of antibiotic reducing/replacing and farming rethinking (e.g., organic acids and copper in feed/biocides) has been scarcely explored. We investigated Salmonella occurrence (conventional and molecular assays) among chicken meat at the processing stage (n = 53 batches/29 farms) and characterized their tolerance to diverse stress factors (antibiotics, copper, acid pH, and peracetic acid). Whole-genome sequencing was used to assess adaptive features and to perform comparative analysis. We found a low Salmonella occurrence (4%) and identified S. Enteritidis/ST11 plus atypical non-H2S-producing S. 1,4,[5],12:i:-/ST3478. The ST3478 presented the ability to grow under diverse stresses (antibiotics, copper, and acid-pH). Comparative genomics among ST3478 isolates showed similar antibiotic/metal resistance gene repertoires and identical nonsense phsA thiosulfate reductase mutations (related to H2S-negative phenotype), besides their close phylogenetic relationship by cgMLST and SNPs. This study alerts for the ongoing national and international spread of an emerging monophasic Salmonella Typhimurium clonal lineage with an enlarged ability to survive to antimicrobials/biocides commonly used in poultry production, being unnoticed by conventional Salmonella detection approaches due to an atypical non-H2S-producing phenotype.